2020
DOI: 10.3390/toxics8040095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3-Month Exposure to E-Cigarette Aerosols on Glutamatergic Receptors and Transporters in Mesolimbic Brain Regions of Female C57BL/6 Mice

Abstract: Electronic cigarettes (e-cigs) use has been dramatically increased recently, especially among youths. Previous studies from our laboratory showed that chronic exposure to e-cigs, containing 24 mg/mL nicotine, was associated with dysregulation of glutamate transporters and neurotransmitter levels in the brain of a mouse model. In this study, we evaluated the effect of three months’ continuous exposure to e-cig vapor (JUUL pods), containing a high nicotine concentration, on the expression of glutamate receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 83 publications
1
7
0
Order By: Relevance
“…They documented lower expression of GLT-1 and xCT in animals exposed for three and six months. Another study revealed that three-month exposure to vapors containing 50 mg/mL nicotine modulated levels of metabotropic glutamate receptors-1 (mGluR1) and mGluR5 expression in the nucleus accumbens shell [28]. In conjunction with this prior data, our findings suggest that as a consequence of reduced glutamate uptake, nicotine could increase the release of glutamate into the synapses in the mesocorticolimbic system.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…They documented lower expression of GLT-1 and xCT in animals exposed for three and six months. Another study revealed that three-month exposure to vapors containing 50 mg/mL nicotine modulated levels of metabotropic glutamate receptors-1 (mGluR1) and mGluR5 expression in the nucleus accumbens shell [28]. In conjunction with this prior data, our findings suggest that as a consequence of reduced glutamate uptake, nicotine could increase the release of glutamate into the synapses in the mesocorticolimbic system.…”
Section: Discussionsupporting
confidence: 70%
“…Glutamate, the principal excitatory neurotransmitter in the human brain, is responsible for cognitive function, cortical excitability, and energy production [24][25][26]. E-cigarette vapor containing nicotine may increase glutamate transmission and modulate postsynaptic glutamate receptors [27,28]. Specifically, nicotine activation of nAChRs influences glutamate production, which leads to increased glutamate neurotransmission [29,30], which in turn contribute to behavioral changes such as drug-seeking behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Acute exposure to Juul aerosols led to impaired endothelial function in rats comparable to cigarette smoke ( Rao et al, 2020 ). Three months of Juul aerosol exposure to mice induced dysregulation of glutamatergic system activity in mesolimbic brain regions, as evidenced by differential effects on several targets of the glutamatergic system in the nucleus accumbens and hippocampus ( Alhaddad et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several published works used computerized delivery machines to deliver e-cigarette vapors in the environments, and the pre-clinical models can then be exposed through inhalation. [1][2][3][4] It has been found that these electronic systems are proper delivery techniques and can produce toxicological effects in pre-clinical models after exposure to concentrations of nicotine-containing vapors. [1][2][3][4][5] The use of e-cigarettes is currently widespread in developed countries.…”
mentioning
confidence: 99%
“…[1][2][3][4] It has been found that these electronic systems are proper delivery techniques and can produce toxicological effects in pre-clinical models after exposure to concentrations of nicotine-containing vapors. [1][2][3][4][5] The use of e-cigarettes is currently widespread in developed countries. The e-cigarette devices release vapors containing nicotine without the chemicals present in conventional cigarettes.…”
mentioning
confidence: 99%